A Longitudinal investigation of the Periodontal changes in adult and adolescent orthodontic patients using bands or bonds on molars (Mustansiria Dental Journal, 2018)
The present study was carried out to evaluate the differences in periodontal response to orthodontic treatment between banded and bonded molar teeth as well as the differences between adults and adolescents.The samples of the study consisted of 50 patients (16 adults and 34 adolescents) who were received full arch orthodontic appliances with banded or bonded molars. Clinical parameters included plaque and gingival indices as well as probing pocket depth were scored at [pretreatment and at 3, 6, 9, 12 months (during treatment) and at the end of the treatment]. The results demonstrated that during and at the end of the treatment, all the parameters were significantly higher for band molars than for analogous bonded molars. Also, the adolescents showed significantly higher levels of all clinical measurements than adults.